All-optical mapping reveals distributed suppression of cortical sensory responses after optogenetic silencing - Manuel Ambrosone; Elena Montagni; Francesco Resta; Tommaso Ulivi; Lorenzo Curti; Federica Polverini; Giacomo Mazzamuto; Guido Mannaioni; Alessio Masi; Francesco Saverio Pavone; Anna Letizia Allegra Mascaro (Brain Stimulation)
Significance: We designed a novel all-optical tool to simultaneously silence neuronal activity at arbitrary sites on the dorsal cortex, and monitor the consequences of the manipulation. Optogenetic inhibition of primary sensory regions determined short and long-term dampening of the sensory response across a distributed cortical network. Introduction: Many fundamental processes of brain computation, such as sensory perception and motor control, heavily rely on the mesoscopic dynamics of activity across the cerebral cortex. Manipulating mesoscale activity and observing its effects across multiple brain regions is crucial for understanding the causal link between cortical dynamics and behavior. Objective: The goal of this study was to develop a novel all-optical system that allows inhibition of excitatory neurons while simultaneously monitoring cortical responses at arbitrary sites across the entire dorsal cortex of mice. Methods: We combined wide-field imaging and optogenetics to create a mesoscale all-optical approach, enabling simultaneous monitoring and manipulation of cortical activity using light. Intravenous injection of two PHP.eB AAVs enabled the whole-brain co-expression of the red-shifted calcium indicator jRCaMP1b and the inhibitory actuator stGtACR2, with stable expression over several weeks. This system was calibrated, and the effects of inhibition on sensory responses were tested. Results: Increasing laser power progressively reduced spontaneous activity at the site of irradiation. A single 5-s pulse on the barrel field cortex significantly decreased the amplitude of sensory-evoked responses, not only in the stimulated region but across the entire stimulated hemisphere. Conclusions: This novel all-optical system enables targeted inhibition while concurrently monitoring mesoscale cortical activity. It provides insights into the dynamics of cortical circuits and offers a milestone for investigating the causal links between neuronal activity and behavior. Future research can use this tool to address sensory responsiveness impairments in neurological and neuropsychiatric disorders.